Effect of the Dimeric Bile Acid Analogue S 0960, a Specific Inhibitor of the Apical Sodium-dependent Bile Salt Transporter in the Ileum, on the Renal Handling of Taurocholate - Schlattjan, Jan Henrik; Fehsenfeld, Heike; Greven, Joachim (Arzneimittelforschung, 2003)
The effect of the dimeric bile acid analogue S 0960 (CAS 142974-51-4), a specific inhibitor of the apical sodium-dependent bile salt transporter (ASBT) in the ileum, on kidney function was studied by clearance experiments in anesthetized rats. Additional experiments were performed on proximal tubular cells freshly isolated from rat kidney cortex and enriched by nycodenz density gradient centrifugation. The clearance studies, which were performed after a 5 h bile duct ligation, revealed a marked rise of the 3H-taurocholate clearance (from 85.4 ±15.7 to 371.1 ± 86.0 µl/min 100g b.w., p < 0.05) and a considerable fall of the fractional tubular 3H-taurocholate reabsorption (from 90.2 ± 1.72 to 68.2 ± 7.50 %, p < 0.05) after S 0960 at a dose of 10 mg/kg i.v whereas the glomerular filtration rate did not significantly change (from 919 ± 165 to 1055 ± 162 µl/ min/100 g b.w). Isolated proximal tubular cells showed a significant accumulation of 3H-taurocholate. The 3H-taurocholate cell/ bath concentration ratio amounted to 3.34 ± 0.17 at a 3H-taurocholate bath concentration of 3 × 10−7 mol/l. LiCl (10−3 mol/l), which is known to inhibit sodium-dependent transport processes in the kidney, markedly diminished cellular 3H-taurocholate uptake (by 65.8 %) whereas probenecid (CAS 57-66-9, 10−4 mol/l), the classical inhibitor of the basolateral organic acid transporter in the kidney, did not significantly affect 3H-taurocholate uptake. This finding indicates that transport of taurocholate by the basolaterally located organic acid transporter is not involved in the uptake process. The kinetic studies revealed an apparent Km value of 31 µmol/l and a Vmax value of 6.7 µmol/l cell water/min for tubular 3H-taurocholate uptake. At concentrations > 30 µmol/l S 0960 virtually completely inhibited cellular 3H-taurocholate uptake. 3H-taurocholate uptake was half-maximally inhibited at a S 0960 concentration of 5.8 µmol/l.The results of this functional study are in line with recent molecular evidence that the apical sodium-dependent bile salt transporters in kidney and ileum are identical and demonstrate that S 0960 is a potent inhibitor of the apical sodium-dependent taurocholate transporter in the kidney which augments the renal clearance of 3H-taurocholate. Compounds such as S 0960 may be of special therapeutical value in patients with extrahepatic cholestasis and elevated levels of plasma bile acids.
Keywords: Apical sodium-dependent bile salt transporter, inhibitor; Bile acid analogue, dimeric; CAS 142974-51-4; S 0960, effect on kidney function, rat; Taurocholate, clearance